Transplanting Marginal Organs in the Era of Modern Machine Perfusion and Advanced Organ Monitoring - Resch, Thomas; Cardini, Benno; Oberhuber, Rupert; Weissenbacher, Annemarie; Dumfarth, Julia; Krapf, Christoph; Boesmueller, Claudia; Oefner, Dietmar; Grimm, Michael; Schneeberger, Sefan (Frontiers in Immunology, 2020)
Organ transplantation is undergoing profound changes. Contraindications for donation have been revised in order to better meet the organ demand. The use of lower quality organs and organs with greater preoperative damage, including such from donation after cardiac death (DCD), has become an established routine, but bares the risk of graft malfunction. This risk is further aggravated by ischemia and reperfusion injury (IRI) in the process of transplantation. These circumstances demand a preservation technology which ameliorates IRI and allows for assessment of viability and function prior to transplantation. Oxygenated hypothermic and normothermic machine perfusion (MP) have emerged as valid novel modalities for advanced organ preservation and conditioning. Ex vivo prolonged lung preservation resulted in successful transplantation of high-risk donor lungs. Normothermic MP of hearts and livers displayed safe (heart) and superior (liver) preservation in randomized controlled trials (RCT). Normothermic kidney preservation for 24h was established recently. Early clinical outcomes beyond the market entry trials indicate bioenergetics reconditioning, improved preservation of structures subject to IRI and significant prolongation of the preservation time. The monitoring of perfusion parameters, the biochemical investigation of preservation fluids and the assessment of tissue viability and bioenergetics function now offer a comprehensive assessment of organ quality and function ex situ. Gene and protein expression profiling, investigation of passenger leukocytes and advanced imaging may further enhance the understanding of the condition of an organ during MP. In addition, MP offers a platform for organ reconditioning and regeneration and hence catalyse the clinical realization of tissue engineering. Organ modification may include immunological modification and the generation of chimeric organs. While these ideas are not conceptually new, MP now offers a platform for clinical realization. Defatting of steatotic livers, modulation of inflammation during preservation in lungs, vasodilatation of livers and hepatitis C elimination have been successfully demonstrated in experimental and clinical trials. Targeted treatment of lesions and surgical treatment or graft modification have been attempted. In this review, we address the current state of MP and advanced organ monitoring and speculate about logic future steps and how this evolution of a novel technology can result in a medial revolution.